Rainfall implications on body size evolution of Aspidoscelis gularis (Squamata: Teiidae) - Pérez-Almazán, Carlos (2017)
Life history traits are highly variable attributes that maximize organisms’s adaptation. The relationship of weight and body size with environmental changes and habitat heterogeneity has been documented in previous reports; and size and body shapes are both considered life history attributes that are associated with rainfall, that boost available resources in the environment. While in Aspidoscelis genus, clutch size and relative mass are mainly associated with latitude and altitude, in Aspidoscelis gularis, winter rainfall favors two reproductive seasons, which may determine season variable clutch size. With the aim to study this, samplings were undertaken from May-July 2013, and May-September 2015. A total of 65 individuals lizards of the Southeast clade were obtained, and body length and interaxilar distance measurements were taken; furthermore, hepatic tissue samples were taken for DNA extraction, which allowed us to analyze phylogenetic relationships through a Bayesian Inference analysis, and subsequently, to apply Phylogenetic Comparative Methods (like phylogenetic signal, phylogenetically independent contrasts and reconstruction of ancestral character). Our results showed that there is a low phylogenetic signal regarding body size and shape, while the phylogenetically independent contrasts and reconstruction of ancestral characters suggest that small body sizes are associated to locations with highest rainfall. This can be associated to an establishment of an early sexual maturity, which reflects the maximum size of adults. Furthermore, according to an ANOVA and ANCOVA, there were statistically significant differences in body size and shape respectively, which promote a system for sexual competition for males and a system for fertility in females. These results were important to determine the effect of rainfall on some life history traits, pointing out that lizards of the Southeast clade, belonging to the A. gularis complex were able to face different selection pressures, determined by the environment.